Outcome of Paediatric Cataract Surgery at Tilganga Institute of Ophthalmology, Nepal - Gurung, Rajya Laxmi; Adhikari, Srijana; Shrestha, Ujjowala Devi; Ruit, Sanduk (Birat Journal of Health Sciences, 2018)
Introduction: Paediatric cataract and aphakia are still a major cause of childhood blindness in developing world due to lack of advanced technology. In developing countries like Nepal, many children still present late due to lack of awareness and financial constraints. Objectives: The objective of this study was to determine the outcome of paediatric cataract surgery in a tertiary eye care centre in Nepal. Methodology: A hospital based prospective, observational study taking 42 patients (77 eyes) aged ≦15 years diagnosed with paediatric cataract were enrolled during a period of 1 year ( Jan 2011 - Jan 2012) at Tilganga Institute of Ophthalmology, Kathmandu, Nepal. The patients underwent either: a) Lens aspiration + Primary posterior capsulotomy (PPC) + Anterior Vitrectomy; b) Lens aspiration + PPC+ Anterior Vitrectomy + Intra-ocular lens (IOL); c) Lens Aspiration + IOL. Post-operatively optical ± amblyopia correction. Statistical analysis was carried out by using STATA 9.0. The association of changes in the vision of eyes before and after surgery was analyzed by using generalization of McNemar's test (Stuart-Maxwell test). A pvalue of < 0.05 was considered for the statistical significance. Institutional Ethics Board approval was obtained from the institutional review committee (IRC) of National Academy Medical Sciences ( NAMS ). Results: Mean age of patients was 4.46 yrs ± 4.32(SD), range from (15 days -12 yrs); Male : Female: 22 (52%)/20 (48%); 35 (83%) patients had bilateral cataract and 7(17%) had unilateral cataract. Morphologically, the most common type of cataract was total cataract (27/32%). Post-operatively, a statistically significant improvement in vision was there in all the eyes ( p value : < 0.0001) . Visual axis opacification was the most common post- operative complication seen in 20(26% ) of total eyes by the end of 6 months. Conclusion: Good visual outcome in paediatric cataract surgery can be obtained in developing countries like Nepal with minimal intra and post-op complications. BJHS 2018;3(1)5 : 331-337